1999
DOI: 10.1093/ajcn/69.4.697
|View full text |Cite|
|
Sign up to set email alerts
|

Longitudinal assessment of energy balance in well-nourished, pregnant women

Abstract: Background: Clinicians often recommend an additional energy intake of 1250 kJ/d to their pregnant patients. Previous studies have shown considerable variation in the metabolic response to pregnancy and thus in the additional energy required to support a pregnancy. Objective: The purpose of this study was to assess how wellnourished women meet the energy demands of pregnancy and to identify factors that predict an individual's metabolic response. Design: Resting metabolic rate (RMR), diet-induced thermogenesis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
110
6
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(128 citation statements)
references
References 41 publications
11
110
6
1
Order By: Relevance
“…Consequently the 24-h recall and 3-day diet record data were combined to provide the mean intake of each nutrient for each woman, in mth4 and mth7 of pregnancy. No correction was made for under-reporting because of the unpredictable changes in basal metabolic rate during pregnancy (Kopp-Hoolihan et al, 1999;Prentice and Goldberg, 2000) and the 73% of subjects suffering from morning sickness in early pregnancy.…”
Section: Methodsmentioning
confidence: 99%
“…Consequently the 24-h recall and 3-day diet record data were combined to provide the mean intake of each nutrient for each woman, in mth4 and mth7 of pregnancy. No correction was made for under-reporting because of the unpredictable changes in basal metabolic rate during pregnancy (Kopp-Hoolihan et al, 1999;Prentice and Goldberg, 2000) and the 73% of subjects suffering from morning sickness in early pregnancy.…”
Section: Methodsmentioning
confidence: 99%
“…The majority of studies used a prospective design (n= 6) with three studies (reported in five articles) using a retrospective design. Study sample size varied from 10 ( Kopp-Hoolihan et al, 1999) to 7174 (Hellerstedt et al, 1998). The included studies varied greatly regarding the information authors reported regarding participant characteristics in terms of age, ethnicity, parity and weight status (see Table 1).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Kopp-Hoolihan et al (1999) reported energy intake using three day food diaries from 10 women during pre-conception (T1) and three trimesters during pregnancy (T1, T2, and T3). The results show a 9% increase (775kJ/day) in total energy intake between T1 and T3.…”
Section: Energy and Macronutrientsmentioning
confidence: 99%
“…This is because we 1) intended to differentiate our study from previous studies, and 2) wanted to prove the effects of supplementation of silk peptides in exercise training. Taken together, it seems that 2 wk of exercise and silk peptide intake increase resting energy expenditure and induce fat oxidation.…”
Section: Resting Metabolic Rate (Rmr)mentioning
confidence: 99%
“…Among these, energy imbalance and inactivity are becoming serious problems. Total energy cost can be divided into three parts, including resting metabolic rate (RMR), diet-induced thermogenesis (DIT), and the amount of energy used for physical activity energy expenditure (AEE) (2). The greatest component of daily energy expenditure is RMR, constituting about 70% of the total energy expenditure (3,4).…”
mentioning
confidence: 99%